Proceedings of the International Working Conference on Advanced Visual Interfaces 2012
DOI: 10.1145/2254556.2254637
|View full text |Cite
|
Sign up to set email alerts
|

Interactive exploration of music listening histories

Abstract: Over the past years, music listening histories have become easily accessible due to the expansion of online lifelogging services. These histories represent the sequence of songs listen by users over time. Although this data contains intrinsic users' tastes and listening behaviors, it has been mainly used to personalize recommendations. Tools to help users exploring and reasoning about the information contained in the listening history, only recently have started to emerge. In this paper we describe a new visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Each of these plots alone carries less information, but their assembly and cross-interactivity allow for complex visual queries and information retrieval. This approach was followed in [3,5,7] and also by Wirfs-Brock et al [19] in an experiment where a few interviewees were exposed to "silent data" extracted from their Spotify listening history in order to help them defining how they would command a voice assistant to choose music. Although our users are different -namely social scientists conducting interviews -this study is inspirational in using simple plots that are easy to understand for any user, even the less "visually literate".…”
Section: A Synthetic Review Of Music Data Visualizationmentioning
confidence: 99%
“…Each of these plots alone carries less information, but their assembly and cross-interactivity allow for complex visual queries and information retrieval. This approach was followed in [3,5,7] and also by Wirfs-Brock et al [19] in an experiment where a few interviewees were exposed to "silent data" extracted from their Spotify listening history in order to help them defining how they would command a voice assistant to choose music. Although our users are different -namely social scientists conducting interviews -this study is inspirational in using simple plots that are easy to understand for any user, even the less "visually literate".…”
Section: A Synthetic Review Of Music Data Visualizationmentioning
confidence: 99%
“…The frequency‐based song‐ranking algorithm is helpful for mood analysis. Dias [DFG12] uses a different timeline‐based layout for the visualization of music‐listening history using stacked dots. Filtering is provided to view only the selected songs and the ranking is purely frequency based.…”
Section: Related Workmentioning
confidence: 99%
“…This problem cannot be solved by increasing the link thickness due to the notable overlapping caused. Some previous works [BSSB10, DFG12] use a circle to represent events. This can also lead to overlaps if there are many events with long duration.…”
Section: Description Of Myeventsmentioning
confidence: 99%
“…The visualization compares two listening histories in a timeline technique using the similarity between two songs and the relevance of the song to the talk. Dias et al developed an approach for browsing listening histories by combining a rich-featured timelinebased visualization with an interactive filtering mechanism, with the goal of helping users to identify trends and habits (6). Their experimental evaluation with users revealed that users were able to infer about their main life events and listening changes, and also promote new behaviors.…”
Section: Related Workmentioning
confidence: 99%